Konsep Hudud Dalam Al-Quran - Fiddini Izaturahmi; Winda Sugiarti; Wismanto Wismanto; Shafiah Shafiah; Melisa Putri (Jurnal Budi Pekerti Agama Islam, 2024)
The laws regulated by Allah in the Qur'an, basically have the aim of realizing and protecting human benefit, both individually and collectively. The Qur'an presents various forms of jinayat, and one of them is jinayat hudud. Shaykhul Islam Ibn Taymiyah Rahimahullah stated that hudud punishment comes from Allah's grace for the welfare of His creatures. The research method used is Library Research. Library Research (Library Research) is research in which data collection is carried out by collecting data from various literature. Etymologically, hudud is defined as a separation or barrier that cannot be crossed because of certain offenses that have punishment. Terminologically, hudud is defined as Allah's prohibition which commands humans to observe it and not approach it. This includes orders to abstain from certain acts that have been regulated and have predetermined penalties. Various Types of Violations of Hudud: Fiqhi scholars understand hudud in a limited and specific sense, which includes categorization of offenses such as adultery, accusation of adultery, theft, vandalism, rebellion, apostasy, and alcohol drinking. Hudud for each of these violations has a predetermined penalty.